2018
DOI: 10.1007/s11302-018-9618-3
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 and P2Y6 receptor activation elicits intracellular calcium responses in human adipose-derived mesenchymal stromal cells

Abstract: Adipose tissue contains self-renewing multipotent cells termed mesenchymal stromal cells. In situ, these cells serve to expand adipose tissue by adipogenesis, but their multipotency has gained interest for use in tissue regeneration. Little is known regarding the repertoire of receptors expressed by adipose-derived mesenchymal stromal cells (AD-MSCs). The purpose of this study was to undertake a comprehensive analysis of purinergic receptor expression. Mesenchymal stromal cells were isolated from human subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…In contrast, P2X6R mRNA and protein levels decrease in the same ASCs committed toward osteogenesis, so that such a variable expression may be critical for early MSCs commitment to differentiate [198]. In more recent studies, in which human ASCs were again investigated, transcripts for multiple purinoreceptors were found, confirming the presence of P2R previously detected [199], besides most adenosine receptors [197]. In these cells, the effects of specific agonists and antagonists suggested that both P2Y1R and P2Y13R were mainly responsive to ADP, while P2Y4R and P2Y11R served as primary UTP and ATP receptors, respectively.…”
Section: Expression Of Purinergic Receptors In Mscssupporting
confidence: 67%
“…In contrast, P2X6R mRNA and protein levels decrease in the same ASCs committed toward osteogenesis, so that such a variable expression may be critical for early MSCs commitment to differentiate [198]. In more recent studies, in which human ASCs were again investigated, transcripts for multiple purinoreceptors were found, confirming the presence of P2R previously detected [199], besides most adenosine receptors [197]. In these cells, the effects of specific agonists and antagonists suggested that both P2Y1R and P2Y13R were mainly responsive to ADP, while P2Y4R and P2Y11R served as primary UTP and ATP receptors, respectively.…”
Section: Expression Of Purinergic Receptors In Mscssupporting
confidence: 67%
“…Recruitment to this lineage gives rise to preadipocytes, which when induced, undergo mitotic clonal expansion and differentiate into adipocytes. It has been reported that human adipose tissue derived MSC express several purinergic receptors (P2X and P2Y series), but with a predominant role for P2Y 2 and P2Y 6 receptors in eliciting intracellular calcium response (54). There is also evidence that purinergic receptors play a role in stem cell differentiation (55).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that activation of P2Y receptors increases PLC activity and IP 3 formation for Ca 2+ signaling (Ciciarello et al, 2013). This is supported by findings in adipose-derived mesenchymal stem cells where ATP induces intracellular Ca 2+ signals via P2Y2 receptors (Ali, Turner, & Fountain, 2018). The family of P2X receptors are ATP-gated ion channels that conduct Na + , K + and Ca 2+ ions (Roberts et al, 2006).…”
Section: Introductionmentioning
confidence: 87%